If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + -1) = 16 Reorder the terms: 2(-1 + m) = 16 (-1 * 2 + m * 2) = 16 (-2 + 2m) = 16 Solving -2 + 2m = 16 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2m = 16 + 2 Combine like terms: -2 + 2 = 0 0 + 2m = 16 + 2 2m = 16 + 2 Combine like terms: 16 + 2 = 18 2m = 18 Divide each side by '2'. m = 9 Simplifying m = 9
| 2p^2+p-4=0 | | 14x^2+78x+40=0 | | 2k^2=-21k-49 | | x^2-14x-5=-4x^2-27x-11 | | 5*-2-8-11*-2=-3*-2-1-5 | | 40x^2=-104x-48 | | z^4-(3+2i)z^2-3i=0 | | 3y+(y+20)=180 | | 3x^2-5x-13=-6x-3 | | 4.9t^2-5.2t-38=0 | | 35x^2-60x=101x+70 | | 2x+(x-12)=180 | | 9t^3=49t | | 7x^2-7-50x=-2x | | 4.9t^2+5.2t+38=0 | | -9y=45-6x | | 19x=-35-2x^2 | | 8a=9a-2(1) | | 4x^2=25x-25 | | 8x+4=-26-2x | | 7x^2-6x+6=0 | | 15x^2+35=46x | | -26-2x= | | 5m-8-11m=-3(m-1)-5 | | 20x-21=4x^2 | | 7x-30=-26 | | 4(2x-3)=-8 | | T(n)=5n+3 | | 7x+4+x=-26-2x | | 2+11x=21x^2 | | 3x-19=-11 | | 2x-6/4 |